Nutritional Status of Pregnant and Lactating Marwari Ewes Grazing on an Arid Rangeland - Mali, P C; Patnayak, B C (Annals of Arid Zone, 2016)
Measurements on intake of nutrients and their digeslihility were mad.: during early pregnancy, advanced pregnancy and lactation of Marwari ewes grazing on an arid rangeland. Chromic oxide was used as an external indicator to determine the faecal output and lignin as an internal indicator to determine the nutrient digestibility. The crude protein of ingested forage was maximum in August (9.5%) and lowest ’4.6%) in January. The digestible crude protein (OCP) and totai digestible nutrients (TDN) of ingested forage varied from 0.47 to 1.53% and 25.2% to 47.4%, respectively. The digestibility of different nutrients was significantly lower during advanced pregnancy as compared to the early pregnancy and lactation. Although the intake of crude protein was adequate, OCP intake was very low i.e. 4.5 to 10.3 g animal/day during different physiological stages. This was due to very low digestibility of protein (6.5 to 16.1%). There was significant increase in the intake of dry matter (DM), crude fibre (CP), nitrogen free extract (NFE) and TON during lactation as compared to early pregnancy and advanced pregnancy. The intake of dry matter was less than the optimum required during advanced pregnancy. Corresponding to OM intake, TDN, intake was also low during the advanced pregnancy. It is due to low digestibility of DM, CF, CP and NFE. The results suggest that during advanced pregnancy of grazing ewes it is essential to supplement high protein and energy feed for better lamb production.